SOCIO-PSYCHOLOGICAL FACTORS OF AGGRESSIVE BEHAVIOR OF ADOLESCENTS - Isaxanova Moxidil Erkinovna (American Journals, 2023)
The article is about some kinds of aggressivety, appearing at teenagers during the period of their forming, and becoming of personality.
Keywords: features of identity of character, state, hormonal phenomenon, aggressive behavior, autism, uneasiness, reaction, disadaptation, psychotherapeutic state, relaxation exercises, role – playing games.